Cortical bone properties in the Brtl/+ mouse model of Osteogenesis imperfecta as evidenced by acoustic transmission microscopy. (February 2019) - Blouin, S.; Fratzl-Zelman, N.; Roschger, A.; Cabral, W.A.; Klaushofer, K.; Marini, J.C.; Fratzl, P.; Roschger, P.
Abstract: Higher skeletal fragility has been established for the Brtl/+ mouse model of osteogenesis imperfecta at the whole bone level, but previous investigations of mechanical properties at the bone material level were inconclusive. Bone material was analyzed separately at endosteal (ER) and periosteal regions (PR) on transverse femoral midshaft sections for 2-month old mice (wild-type n = 6; Brtl/+ n = 6). Quantitative backscattered electron imaging revealed that the mass density computed from mineral density maps was higher in PR than in ER for both wild-type (+2.1%, p < 0.05) and Brtl/+ mice (+1.8%, p < 0.05). Electron induced X-ray fluorescence analysis indicated significantly lower atomic Ca/P ratios and higher Na/Ca, Mg/Ca and K/Ca ratios in PR bone compared to ER independently of genotype. Second harmonic generation microscopy indicated that the occurrence of periodically alternating collagen orientation in ER of Brtl/+ mice was strongly reduced compared to wild-type mice. Scanning acoustic microscopy in time of flight mode revealed that the sound velocity and Young's modulus (estimated based on sound velocity and mass density maps) were significantly greater in PR (respectively +6% and +15%) compared to ER in wild-type mice but not in Brtl/+ mice. ER sound velocity and Young's modulus were significantly increased in Brtl/+ mice (+9.4% and +22%, respectively) compared to wild-type mice. These data demonstrate that the Col1a1 G349C mutation in Brtl/+ mice affects the mechanical behavior of bone material predominantly in the endosteal region by altering the collagen orientation. Graphical abstract: Highlights: endosteal and periosteal apposed bone have different composition in mouse femur. collagen mutation in Brtl/+ mouse affects the mechanical behavior of femoral bone. mechanical alteration due to degradation of collagen fibers orientation.